Intercultural learning in pandemic era - Eripuddin, Eripuddin; Jufrizal, Jufrizal; Agustina, Agustina (Linguistics and Culture Review, 2022)
This study investigated the students' intercultural learning in online classes during the pandemic era. The purpose of this study was to find out the reflection of intercultural learning in the EFL language of sixth-semester students of the English Study Program at Pasir Pengaraian University. This research was descriptive qualitative. The sample of this study was 30 students. The instruments of collecting data were questionnaires and interviews. This study shows that the students' intercultural learning was reasonable. In the teaching and learning process, there was no misunderstanding about the nature or actions of students from different cultural and language backgrounds in teaching and learning activities. Indeed, the process of teaching and teaching runs well. Each student could communicate well and make a good relationship with other people from different cultures. In short, students could develop a broader understanding of their language and cultural differences in the teaching and learning process during the pandemic era.